2013
DOI: 10.1007/s13201-013-0114-1
|View full text |Cite
|
Sign up to set email alerts
|

Application of sharing genetic algorithm for optimization of groundwater management problems in Wadi El-Farigh, Egypt

Abstract: Management of groundwater resources is very important for regions where freshwater supply is naturally limited. Long-term planning of groundwater usage requires method-based new decision support tools. These tools must be able to predict the change in the groundwater storage with sufficient accuracy and must allow exploring management scenarios with respect to different criteria such as sustainability and cost. So, a multi-objective optimization algorithm is used for groundwater management problem. In this pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The results showed that under the increasing of pumping rate by 25 %, the optimal pumping rate and drawdown ranged from 638 138 to 595 978 m 3 day −1 and from 4. that the optimal pumping rate and the corresponding drawdown range from 190 699 to 179 423 m 3 day −1 and 6.13 to 8.34 m respectively. Gad and Khalaf (2013) used MOGA model to develop the maximum pumping rate and minimum operation cost as well as to predict the future changes in both pumping rate and pumping operation cost in the Miocene aquifer of Wadi El-Farigh, West Delta, Egypt. They concluded that the compromise solution among the set of Pareto optimal solutions for the three proposed scenarios in MAIWF at year 2050 are optimal pumping of 576 130 m 3 day −1 with optimal cost of USD 533 332 for the first scenario, optimal pumping of 667 130 m 3 day −1…”
Section: Back Closementioning
confidence: 99%
“…The results showed that under the increasing of pumping rate by 25 %, the optimal pumping rate and drawdown ranged from 638 138 to 595 978 m 3 day −1 and from 4. that the optimal pumping rate and the corresponding drawdown range from 190 699 to 179 423 m 3 day −1 and 6.13 to 8.34 m respectively. Gad and Khalaf (2013) used MOGA model to develop the maximum pumping rate and minimum operation cost as well as to predict the future changes in both pumping rate and pumping operation cost in the Miocene aquifer of Wadi El-Farigh, West Delta, Egypt. They concluded that the compromise solution among the set of Pareto optimal solutions for the three proposed scenarios in MAIWF at year 2050 are optimal pumping of 576 130 m 3 day −1 with optimal cost of USD 533 332 for the first scenario, optimal pumping of 667 130 m 3 day −1…”
Section: Back Closementioning
confidence: 99%
“…), using analytic element models to simulate an aquifer under limited and special conditions (Gaur et al, 2011;Majumder and Eldho, 2016, and etc. ), use meta-models to communicate between simulation and optimization models (Rogers and Dowla, 1994;Karamouz et al, 2007;Tabari, 2015;Alizadeh et al, 2017), create or modify MODFLOW and MT3DMS codes (Wang and Zheng, 1994;GAD and Khalaf, 2013;Elci and Tamer Ayvaz, 2014;Sreekanth et al, 2015;Luo et al, 2016;Ayvaz, 2016;Ghaseminejad and Shourian, 2019;Norouzi Khatiri et al, 2020 , and etc. ).…”
Section: Introductionmentioning
confidence: 99%
“…Saafan et al, (2011) applied multi-objective genetic algorithm (MOGA) Code in El-Farafra depression, Egypt to study the maximum pumping rate and minimum operation cost. Gad and Khalaf, (2013) used MOGA model to develop the maximum pumping rate and minimum operation cost in the Miocene aquifer of Wadi El-Farigh, West Delta, Egypt.…”
Section: Introductionmentioning
confidence: 99%